Newman's Error Analysis: The Students' Errors in Solving Word Problems of Proportion - Indriana, Indriana; Pathuddin, Pathuddin; Lefrida, Rita; Alfisyahra, Alfisyahra (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Kerinci, 2024)
Students' errors in solving mathematical problems need to be analyzed in depth so that teachers can choose the right way to anticipate the repetition of the same errors. This study aims to reveal the types of errors made by students in solving word problems on the topic of proportion. This study is a descriptive study with a qualitative approach. The subjects involved were two seventh grade students, male and female. The results of this study indicate that based on Newman's error analysis, male subjects mainly made reading errors, errors in understanding the problem, transformation errors, and writing the final answer that did not include a conclusion. While female subjects made errors in understanding the problem, choosing the operation used, and writing the conclusion sentence in the final answers. The results of this study can help students understand the errors made so that the errors are not repeated and can be input for teachers in improving the learning process.